Molecular Simulation Elaborating the Mechanism of 1β-Hydroxy Alantolactone Inhibiting Ubiquitin-Conjugating Enzyme UbcH5s - Xu, Youdong (Sci Rep, 2020)
1β-hydroxy alantolactone, a sesquiterpene lactone, exhibits potent anti-inflammatory and anticancer activities. Recently, it has been found to target UbcH5s by covalently bonding with Cys85 specifically, but the exact molecular basis remains unclear. Here, we analyzed the structural specificity of the catalytic site of UbcH5s by comparing them with other E2 proteins. Molecular dynamics was performed to detect the structural stability of the catalytic site. Docking method was then used to predict conformations of ligand docked at the catalytic site of UbcH5s. The electrostatic surface and charge distribution of ligand and proteins were analyzed by quantitative calculation. Molecular dynamics was used to detect the stability of docking complexes of 1β-hydroxy alantolactone and UbcH5s, the covalently bonded intermediates and the products. The QM/MM methodology was used to calculate the free energy barrier of hydrogen transfer and formation of covalent bond between 15-position carbon of ligand and Cys85. Results revealed that the structure of the catalytic site is stable, and 1β-hydroxy alantolactone can dock at the catalytic site with correct conformation. Molecular dynamics further demonstrates that 1β-hydroxy alantolactone can steadily combine with UbcH5s. Intermediate and product of catalytic reaction are also certified to be stable. Besides, Asp112 and Asn114 function as anchors to fix ligand, ensuring it steadily docked at catalytic site to complete covalent reaction. More importantly, we have found that Cys85 of UbcH5c is more efficient to form a covalent bond with the ligand in comparison with UbcH5a and UbcH5b. Our results successfully explained the mechanism of 1β-hydroxy alantolactone covalently bonding with UbcH5s. Such molecular mechanism may provide a better insight into the molecular development or modification for ubiquitin-related drugs.